2014
DOI: 10.1017/s0007485314000285
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hymenopteran larval and egg parasitoids to control stored-product beetle and moth infestation in jute bags

Abstract: The control of stored-product moths in bagged commodities is difficult because the developmental stages of the moths are protected by the bagging material from control measures such as the application of contact insecticides. Studies were carried out to assess the ability of Hymenopteran parasitoids to locate their hosts inside jute bags in the laboratory. The ability of different parasitoids to penetrate jute bags containing rice was investigated in a controlled climate chamber. Few Habrobracon hebetor (Say) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Females visit trees for oviposition and have a much higher chance of being trapped in resin than males. Members of the family Ptinidae, a common host group of Cerocephalinae (Adarkwah et al 2014), are closely associated with resin-producing trees and rank among the four most abundant beetle families in Baltic amber (Bukejs and Alekseev 2015). Other known hosts for Cerocephalinae are ambrosia beetles (Curculionidae: Platypodinae), which are diverse and common inclusions in Dominican amber (Peris et al 2015) and were found as syninclusions of Dominocephala vibrissae (Krogmann 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females visit trees for oviposition and have a much higher chance of being trapped in resin than males. Members of the family Ptinidae, a common host group of Cerocephalinae (Adarkwah et al 2014), are closely associated with resin-producing trees and rank among the four most abundant beetle families in Baltic amber (Bukejs and Alekseev 2015). Other known hosts for Cerocephalinae are ambrosia beetles (Curculionidae: Platypodinae), which are diverse and common inclusions in Dominican amber (Peris et al 2015) and were found as syninclusions of Dominocephala vibrissae (Krogmann 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All species are assumed to be parasitoids of small endophytic beetles (Bouček 1988), which makes them potentially potent biological control agents. Members of the genera Cerocephala and Theocolax have hereby proven to be effective against pests like Stegobium paniceum Linnaeus, 1758, Rhyzopertha dominica Fabricius, 1792 and other crop-feeding beetles (Flinn and Hagstrum 2002, Adarkwah et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that host location outside the commodity is strongly influenced by factors such as light and that the number of wasps released should be higher than the number recommended for use inside the commodity. Additional research on dispersal and host finding was conducted by Adarkwah et al who looked at the ability of L. distinguendus to reach hosts inside jute bags and bulk maize [68,69]. They showed that the wasps, depending on mesh size, are able to penetrate the bags and reduce pest infestations by 81%, while reduction was about 37% one meter inside the maize bulk.…”
Section: From the Late 1990s–presentmentioning
confidence: 99%
“…Biological control may provide an affordable and sustainable option for reducing losses to pests in stored food products (Bellows, ; Shin et al., ; Adarkwah et al., ). The use of natural enemies to control insect pests in storage situations is not a new concept, but it has only recently received serious attention – pathogens, parasitoids, and predators have been investigated in the context of stored product protection (Schöller & Flinn, ; Adarkwah et al., , , , , ; Adarkwah & Schöller, ; Flinn & Schöller, ). Currently, modern protection of stored products is seeking to apply biocontrol strategies such as the combination of predators and parasitoids, which would eventually become an integral part of the integrated pest management (IPM) approach, especially in Africa where stored‐product insect pests concurrently infest stored grains.…”
Section: Introductionmentioning
confidence: 99%